East Asia imperilled : transnational challenges to security - Dupont, Alan. (Cambridge ; New York : Cambridge University Press, 2001)
Security issues have traditionally been defined in military terms, yet the post-Cold War security landscape contains numerous non-military challenges to security. In this pathbreaking analysis, Alan Dupont argues that an emerging new class of non-military threats has the potential to destabilize East Asia and reverse decades of hard-won economic and social development. He shows that these transnational shifts must be grasped and dealt with by governments and non-government organizations both regionally, and internationally, if conflict is to be avoided. Transnational threats stem from overpopulation, deforestation and pollution, global warming, unregulated population movements, transnational crime, virulent new strains of infectious diseases and other issues not previously associated with international security. Collectively they represent a new agenda and pose novel challenges for foreign and defence policy. This highly informative, compelling and authoritative book is essential reading for East Asia specialists and makes a significant and timely contribution to international security debates.Anette Bremer a o
1. Transnational Issues and Security -- Pt. I. Environmental Scarcity -- 2. Population and Conflict -- 3. Deforestation, Pollution and Climate Change -- 4. Will There Be an Energy 'Gap'? -- 5. Is a Food Crisis Likely? -- 6. Water Wars -- Pt. II. Unregulated Population Movements -- 7. Unregulated Population Movements, Ethnic Conflict and the State -- 8. People-smuggling, Undocumented Labour Migration and Environmental Refugees -- Pt. III. Transnational Crime and AIDS -- 9. Transnational Crime -- 10. Drug-trafficking - An Emerging Threat -- 11. The AIDS 'Pandemic'.
Includes bibliographical references and index.
Keywords: Environmental degradation -- Political aspects; Environmental degradation -- Social aspects; National security -- East Asia; East Asia -- Environmental conditions; East Asia -- Population; East Asia -- Social conditions